KEJANG DEMAM PADA ANAK - SP, Wayan Sulaksmana; Sukardi, Sukardi; Dalimunte, Abdul Razak (Jurnal Kedokteran, 2013)
Febrile convultion is a neurological disorder that is often found in children. Fever is usually caused by an infection outside of the central nervous system such as : Upper respiratory tract infection,gastroenteritis, urinary tract infection, etc. Febrile siezures in general brief form : tonic, tonic-clonic,focal or partial. Febrile convultion should receive prompt and appropriate treatment because of delays and procedural errors would cause sequel and death. Appropriate education for parents about febrile convultion is unbelievably necessary to reduce anxiety. Keywords : seizure,fever,anticonvulsanst